Influenza A induced cellular signal transduction pathways - Michael, Paul; Brabant, Danielle; Bleiblo, Farag; Ramana, Chilakamarti V.; Rutherford, Michael; Khurana, Sandhya; Tai, T.C.; Kumar, Anand; Kumar, Aseem (Journal of Thoracic Disease; Vol 5, Supplement 2 (August 15, 2013): Journal of Thoracic Disease (Emerging infectious respiratory disease & the 10th Anniversary of SARS Epidemics), 2013)
Influenza A is a negative sense single stranded RNA virus that belongs to the Orthomyxoviridae Family. This enveloped virus contains 8 segments of viral RNA which encodes 11 viral proteins. Influenza A infects humans and is the causative agent of the flu. Annually it infects approximately 5% to 15% of the population world wide and results in an estimated 250,000 to 500,000 deaths a year. The nature of influenza A replication results in a high mutation rate which results in the need for seasonal vaccinations. In addition the zoonotic nature of the influenza virus allows for recombination of viral segments from different strains creating new variants that have not been encountered before. This type of mutation is the method by which pandemic strains of the flu arises. Infection with influenza results in a respiratory illness that for most individuals is self limiting. However in susceptible populations which include individuals with pre-existing pulmonary or cardiac conditions, the very young and the elderly fatal complications may arise. The most serious of these is the development of viral pneumonia which may be accompanied by secondary bacterial infections. Progression of pneumonia leads to the development of acute respiratory distress syndrome (ARDS), acute lung injury (ALI) and potentially respiratory failure. This progression is a combined effect of the host immune system response to influenza infection and the viral infection itself. This review will focus on molecular aspects of viral replication in alveolar cells and their response to infection. The response of select innate immune cells and their contribution to viral clearance and lung epithelial damage will also be discussed. Molecular aspects of antiviral response in the cells in particular the protein kinase RNA dependent response, and the oligoadenylate sythetase RNAse L system in relation to influenza infection.